Examining US monetary spillover to Indonesian local currency government bonds in volatile periods - Muhammad Fajar Nugraha (Asian Development Bank Institute (ADBI), 2023)
This study analyzes the magnitude of the US monetary policy spillover on the Indonesian local currency government bond yield, particularly when the Federal Reserve (Fed) implemented the quantitative easing (QE), tapering off, Fed fund rate (FFR) normalization, and quantitative tightening over the past decades. Understanding the global economic dynamics, such as changes in US monetary policy, can be a critical policy input to mitigate risks in the Indonesian economy, particularly in anticipating the monetary normalization policy amidst COVID-19 uncertainty. Changes in US monetary policy in the form of tapering off, increasing the FFR, and quantitative tightening as an external phenomenon that can affect the yield of Indonesian local currency government bonds. [...]
Keywords: E50; E52; F40; 330; bond yield; federal fund rate; US monetary policy; tapering; quantitative tightening